Long non-coding RNA and Polycomb: an intricate partnership in cancer biology - Achour, Cyrinne; Aguilo, Francesca (Frontiers in bioscience (Landmark. Print), 2018)
High-throughput analyses have revealed that the vast majority of the transcriptome does not code for proteins. These non-translated transcripts, when larger than 200 nucleotides, are termed long non-coding RNAs (lncRNAs), and play fundamental roles in diverse cellular processes. LncRNAs are subject to dynamic chemical modification, adding another layer of complexity to our understanding of the potential roles that lncRNAs play in health and disease. Many lncRNAs regulate transcriptional programs by influencing the epigenetic state through direct interactions with chromatin-modifying proteins. Among these proteins, Polycomb repressive complexes 1 and 2 (PRC1 and PRC2) have been shown to be recruited by lncRNAs to silence target genes. Aberrant expression, deficiency or mutation of both lncRNA and Polycomb have been associated with numerous human diseases, including cancer. In this review, we have highlighted recent findings regarding the concerted mechanism of action of Polycomb group proteins (PcG), acting together with some classically defined lncRNAs including ( ), ( ), ( ), and ( ).